2015
DOI: 10.3892/mmr.2015.4279
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture promotes neural stem cell proliferation and neurogenesis in the dentate gyrus of rats following stroke via upregulation of Notch1 expression

Abstract: Abstract. Neural stem cells (NSCs) are important in rehabilitation following stroke. Electroacupuncture (EA) treatment has been observed to promote the recovery of neurological functions subsequent to stroke, however, the effects of EA on the proliferation and differentiation of NSCs and its potential mechanisms remain to be elucidated. In the present study, rats, in which a stroke was induced through middle cerebral artery occlusion (MCAO), were treated with EA or control manipulation for 21 days. The modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…1I, K). This inconsistency might be ascribed to some factors induced by hypoxia that are involved in hypoxia-induced neurogenesis such as Notch 1 signaling [33][34][35]. Notch 1 is known to be crucial for the self-renewal and fate-decision of NSCs and promotes ischemia-induced neurogenesis in the hippocampus by cleaving Notch 1 and increasing the level of NICD (notch intracellular domain), the active form of Notch 1 that translocates to the nucleus and regulates transcription [36,37].…”
Section: Pfk-1 Reduces the Neuronal Differentiation Of Nscs After Hypmentioning
confidence: 95%
“…1I, K). This inconsistency might be ascribed to some factors induced by hypoxia that are involved in hypoxia-induced neurogenesis such as Notch 1 signaling [33][34][35]. Notch 1 is known to be crucial for the self-renewal and fate-decision of NSCs and promotes ischemia-induced neurogenesis in the hippocampus by cleaving Notch 1 and increasing the level of NICD (notch intracellular domain), the active form of Notch 1 that translocates to the nucleus and regulates transcription [36,37].…”
Section: Pfk-1 Reduces the Neuronal Differentiation Of Nscs After Hypmentioning
confidence: 95%
“…[ 23 ] Animal experiments have confirmed that continuous EA stimulation can improve the cerebral blood flow, confront free radical damage, inhibit cell apoptosis, reduce nerve cell damage, regulate neurotransmitters, promote angiogenesis, regulate vasoactive substances, promote secretion and metabolism of brain neurotransmitters, and regulate the inhibitory status of the ischemic cortex, thus increasing its compensatory function, promoting the ordering of EEG activities, and improving the basic electrical activities of the cortical cells. [ 24 25 26 27 ] The experimental rats' brain perception capacity can thus be increased, their brain execution function is enhanced, and their ability of processing external information and regulating behaviors are also promoted. In this study, we have found that the P latency in the M/ACI rats is shortened, while the amplitude is increased, and the learning-memory ability in the Y-maze is also improved.…”
Section: Discussionmentioning
confidence: 99%
“…Pretreatment or treatment of EA worked against cerebral ischemia and reperfusion damage through regulation of neuronal excitotoxicity, apoptosis, oxidative stress, and inflammation in ischemic stroke [ 37 39 ]. It had also been shown that EA took definite benefits on the improvement of neural repairing after stroke [ 40 42 ]. In addition, the study by Chuang et al stated that EA intervention at the acute stage of TBI resulted in a decrease of transforming growth-interacting factor in injured area and an increase of the regional cerebral blood flow in rats, which contributed to reduce neuronal apoptosis and improve neurological outcomes posttrauma [ 43 ].…”
Section: Discussionmentioning
confidence: 99%